Copper Selenide (CuSe and Cu2Se) Nanocrystals: Controllable Synthesis Through a Facile Ultrasonic Chemical Route - Hu, Hanmei; Ge, Xinqing; Deng, Chonghai; Sun, Mei; Xuan, Han; Zhang, Kehua (Asian Journal of Chemistry, 2013)
Copper selenide (CuSe nanoflakes, Cu2Se nanoearthworms) nanocrystals have been successfully fabricated using hydrazine hydrate as a reducing agent through an ultrasonic-assisted chemical route in one-pot solution. The as-prepared products are characterized by X-ray diffraction, field-emission scanning electron microscopy, transmission electron microscopy and UV-visible absorption spectrum. The experimental results reveal that the appropriate reaction molar ratio of copper salt to selenium powder in the solution plays a critical role in controlling the phase and morphology of copper selenide. The chemical reaction processes for explaining the formation of copper selenide are simply studied. UV-VIS absorption spectra indicate that the synthesized flake-shaped CuSe and earthworm-like Cu2Se nanocrystals have good optical properties.